Effects of retention policy in the performance of BS Accountancy students in Pamantasan ng Lungsod ng Maynila - Kathleen Faye Aragon, Kimberly Grace de Asis, Fritzie Ann Nido, Graham Serapio and Angela Camille Talenjale. 4 0 16; 5
u
Thesis: (Bachelor of Science in Accountancy)- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2